Oral administration of soluble β‐glucans extracted from Grifola frondosa induces systemic antitumor immune response and decreases immunosuppression in tumor‐bearing mice. Issue 1 (15th February 2013) - Masuda, Yuki; Inoue, Hiroko; Ohta, Hiroya; Miyake, Ayumi; Konishi, Morichika; Nanba, Hiroaki
<x xml:space="preserve">Abstract</x> Maitake D (MD)‐Fraction is a highly purified soluble β‐glucan derived from Grifola frondosa (an oriental edible mushroom). Intraperitoneal (i.p.) injection of MD‐Fraction has been reported to inhibit tumor growth via enhancement of the host immune system. In this study, we demonstrated that oral administration of MD‐Fraction as well as i.p. injection significantly inhibited tumor growth in murine tumor models. After oral administration, MD‐Fraction was not transferred to the blood in its free form but was captured by antigen‐presenting cells such as macrophages and dendritic cells (DCs) present in the Peyer's patch. The captured MD‐Fraction was then transported to the spleen, thereby inducing the systemic immune response. Our study showed that MD‐Fraction directly induced DC maturation via a C‐type lectin receptor dectin‐1 pathway. The therapeutic response of orally administered MD‐Fraction was associated with (i) induced systemic tumor‐antigen specific T cell response via dectin‐1‐dependent activation of DCs, (ii) increased infiltration of the activated T cells into the tumor and (iii) decreased number of tumor‐caused immunosuppressive cells such as regulatory T cells and myeloid‐derived suppressor cells. Our preclinical study suggests that MD‐Fraction is a useful oral therapeutic agent in the management of patients with cancer.